PENGARUH PESTISIDA NABATI BUAH CABAI (Capsicum annuum L) DAN UMBI BAWANG PUTIH (Allium sativum L) TERHADAP MORTALITAS HAMA BAWANG MERAH (Spodoptera exigua Hubner) - Nursam, Nursam; Yunus, Mohammad; Nasir, Burhanuddin (AGROTEKBIS, 2018)
Onions (Allium cepa) is one type of horticultural commodities which has great opportunities in the agribusiness sector. The purpose of this study was to determine the effect of botanical pesticide made from chilly (C. annuum) and garlic (A. sativum) on mortality of larvae of S. exigua. The research was carried out in the Laboratory of Plant Pests, Faculty of Agriculture, Tadulako University. The study took place from September to December 2015. This study used a completely randomized design (CRD) with seven treatments; each treatment was repeated three times so there were 21 experimental units. The composition of the treatment were as follows: Control (water only, p0), 2ml fresh chili/100 mlwater (p1),4 ml rotten chili/100 ml water (p2),6 ml fresh garlic/100 ml water (p3), 8 ml rotten garlic/100 ml water (p4), 10 ml mixed of rotten garlic and rotten chili /100 ml water (p5), 12 ml mixed of fresh chili and fresh garlic/100 ml water (p6). Highest rate of S. exiguaÂ  mortality was found in the p5 treatment ranging from 83% - 96% at three to four days of the treatment application. It suggest that this application is very effective in controlling the larvae of S .exigua in onion leaves.Keywords: Mortality, Spodoptera exigua Hubner, and Vegetable pesticides.